The Effect of Profitability, Debt Level, and Company Size on Tax Avoidance - Nicol Manapa, Felisia; Yulazri, Yulazri (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This study aims to evaluate the impact of profitability, debt levels, and company size as independent variables on tax avoidance as the dependent variable. Profitability is measured using Return on Assets (ROA), debt levels are analyzed through Debt to Equity Ratio (DER), and company size is assessed using Sales Growth (SG). The research focuses on the Food & Beverage subsector listed on the Indonesia Stock Exchange for the period 2021-2023. Sampling is conducted using purposive sampling, selecting companies that have profits reported in their financial statements for three consecutive years. The findings indicate that profitability and debt levels have a significant positive impact on tax avoidance, while company size has a significant negative impact on tax avoidance.